2018
DOI: 10.1002/ange.201808216
|View full text |Cite
|
Sign up to set email alerts
|

Selective Boryl‐Anion Migration in a Vinyl sp2−sp3 Diborane Induced by Soft Borane Lewis Acids

Abstract: An intramolecular 1,2-boryl-anion migration from boron to carbon has been achieved by selective activation of the p system in [(vinyl)B 2 Pin 2 )] À using "soft" BR 3 electrophiles (BR 3 = BPh 3 or 9-aryl-BBN). The soft character is key to ensure 1,2-migration proceeds instead of oxygen coordination/B À Oactivation. The BR 3 -induced 1,2-boryl-anion migration represents at riple borylation of av inyl Grignardr eagent using only B 2 Pin 2 and BR 3 and forms differentially protected 1,1,2-triborylated alkanes.N … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 46 publications
1
4
0
Order By: Relevance
“…These results indicate that the cascade does not occur through a radical process. Considering these findings and Inglesons work, [14] we suggest the following mechanism (Scheme 5 c). ICH 2 Bpin acts as soft Lewis acid, which triggers the first 1,2-migration of the boron ate complex 2.…”
supporting
confidence: 70%
See 1 more Smart Citation
“…These results indicate that the cascade does not occur through a radical process. Considering these findings and Inglesons work, [14] we suggest the following mechanism (Scheme 5 c). ICH 2 Bpin acts as soft Lewis acid, which triggers the first 1,2-migration of the boron ate complex 2.…”
supporting
confidence: 70%
“…[13] In 2018, Ingleson and co-workers demonstrated that soft boron-based Lewis acids (BPh 3 and 9-Ph-BBN) induce 1,2-boron migration of a vinyl diboron ate complex to enable the one-pot synthesis of 1,1,2-triborylated alkanes (Scheme 1 b). [14] Inspired by this reaction, we envisioned that commercially available ICH 2 Bpin would react with vinyl boron ate complexes to form 1,3-bis-(boryl)alkanes (Scheme 1 c, pin = pinacolato). We considered that ICH 2 Bpin acting as a soft electrophile would induce a Zweifel-type 1,2-R M -migration of a vinyl boron ate complex to form the 1,2-diborylated alkane intermediate I that might engage in a subsequent Matteson rearrangement [6b] to afford a 1,3-bis-(boryl)alkane.…”
mentioning
confidence: 99%
“…We have also taken the 11 B-NMR, which supports the probable mechanism by observing three different peaks (10.85, 33.04, 36.22) from the crude reaction mixture (Supplementary Fig. 25) 46,47 . The presence of IM-7 was further confirmed by HRMS data and 11 B-NMR data.…”
Section: Articlementioning
confidence: 54%
“…[11] Among various organoboron compounds, gem-bis-(boryl)alkanes have drawn increasing attention in recent years due to their unique reactivity in both catalytic and noncatalytic processes to access value-added chemicals. [16] This transformation is conceptually related to the Zweifel reaction, but the use of such boron "ate" complex can make Bpin act as am igrating group.Notably,this Lewis acid-induced reaction was sensitive [15] Very recently,I ngleson and coworkers demonstrated a1 ,2-metalate rearrangement of avinyl diboronate complex induced by soft boranes including BPh 3 and 9-Ph-BBN ( Figure 1b).…”
mentioning
confidence: 99%